EVIDENCE FOR 17TH-CENTURY TSUNAMIS GENERATED ON THE KURIL-KAMCHATKA SUBDUCTION ZONE, LAKE TOKOTAN, HOKKAIDO, JAPAN - Sawai Y. (My University, 2002)
In the seventeenth century, two tsunamis that were generated by earthquakes on the Kuril-Kamchatka subduction zone inundated the eastern coast of Hokkaido, northern Japan. Stratigraphic evidence for these two tsunamis and related land-level change in coastal Hokkaido consists of two landward-thinning sand layers in the sediments of Lake Tokotan, a coastal lagoon on the Hokkaido coast. The marine origin of these sand layers is indicated by the presence of brackish-marine diatoms. The rarity and high degree of fragmentation of diatom valves suggests that the sands were transported in a short time over a considerable distance. Tsunamis at this site were probably generated by great earthquakes along the Kuril-Kamchatka Trench. Volcanic ash deposits lying just above the sands suggest that tsunamis occurred in the late 17th century. Tsunamis during the historic period are not recorded in Lake Tokotan, which suggests that the sand layers were deposited by tsunamis substantially larger than historic tsunamis.
Keywords: DIATOMS; FRESHWATER COASTAL LAGOON; LAKE DEPOSITS; TEPHROCHRONOLOGY; TSUNAMI